Synthesis of a Cyclic 3-Methylsulfonyl Enol Ether - Bennua-Skalmowski, Baerbel; Vorbrueggen, Helmut (Synthesis, 2015)
Electrophilic introduction of a methylmercapto group into dihydropyran gives 3-methylmercaptodihydropyran, which is readily oxidized to 3-methylsulfonyldihydropyran.
Keywords: enol ether; methylmercapto; methylsulfonyl; methylsulfinyl; oxidation; Oxone